Hardware Implementations of the Lightweight Welch-Gong Stream Cipher Family using Polynomial Bases - Sattarov, Marat (University of Waterloo, 2019)
In this thesis we develop a parametrized generic hardware implementation for the Welch-Gong (WG) stream cipher family for low power and low cost applications. WG stream ciphers operate over finite fields, and are comprised of Linear Feedback Shift Register (LFSR) and non-linear WG transformation as filtering function. These stream ciphers provide mathematically proven keystream properties. We begin with design of individual components that perform cryptographic functions. Then we construct WG transformation using these components and perform analysis of dependency between de- sign parameters and circuit area pre place-and-route for ASIC and two FPGAs. We also explored a second implementation approach that uses constant arrays or lookup tables generated with GAP by Zidaric. Finally, instances of the complete cipher of different sizes from WG-5 to WG-16 that output from 1 to 32 bits / cycle are shown, and their performance and area is analyzed for 65nm CMOS technology post place-and-route.
Keywords: stream cipher; encryption; communication; security; VHDL; digital; hardware; WG; Welch-Gong